Newborn at a Distance in Hospital: Review on Positive Effect of Humanized Care on Developmental Outcome Parameters - Bhosale, Vaibhav; Radha, Vaidyanathan; Shelar, Sangita; Savita Ingale; Shinde, Avinash; Gadekar, Nitin (Innovational: Journal of Nursing and Healthcare, 2024)
In a methodological approach, this best evidence review article commences with a fleeting trail of human life as it begins in health-care environment. It provides an explorative overview of various clinical research study results undertaken on newborns in a rural tertiary care hospital. The second section considers six different research approaches to “humanized care of newborns” toward enhancing developmentally supportive care that has the potential to positively affect outcome parameters in spite of the criticality of illness. Significant supportive evidence was observed through clinical interventions that promote baby-friendly attitude, gentle handling and positioning of newborns as a routine, and feeding with increased mothers’ milk when needed for newborns under phototherapy, maintained physiological stability. Moreover, providing rhythmic gentle, tactile, kinesthetic stimulation, giving massage with traditional oils and patterns, establishing auditory, vestibular, olfactory, and visual system stimulation improved outcome prognosis of both normal and critically ill newborns. This moment in time when social distancing is becoming a daily norm, “technological world” needs “humanizing” more than ever. Because there is a need to reinvigorate a movement that can incorporate nature, art, and science in hospitals so that newborns are not kept at “distance” from nurses, doctors, and parents physically, physiologically, psychologically, socially, and emotionally for care without compromising quality and medical requirements. Such an approach to treat each newborn as a unique individual stimulates the ecology around as well ensure maximum comfort to overcome painful and an alien like environment faced by baby on its transport from womb to extra uterine life.